2011
DOI: 10.2149/tmh.2011-01
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Sources and Some Unsual Manifestations of Lead Poisoning in a Tropical Developing Country

Abstract: Lead-containing cooking utensils, sometimes used in South Indian homes, and indigenous medications, widely used in India and increasingly in developed countries, may be responsible for lead intoxication in adults. We report chronic lead poisoning in five adult patients. Not all patients had abdominal colic, while dramatic weight loss, depression and encephalopathy were seen. Once recognized, lead poisoning is treatable and sometimes preventable. Response to chelation therapy with agents such as calcium ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Lead had been detected in blood samples of children, pregnant women, battery workers and painters above the permissible limit in many developing countries including India [15,16]. Moreover, high lead contamination in soil [17], water [18], air [19], herbal products [20], lead acid batteries [21], paints [22], cosmetics mainly (Kohl, lipsticks sindoor, hair dye) [23], and utensils have been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…Lead had been detected in blood samples of children, pregnant women, battery workers and painters above the permissible limit in many developing countries including India [15,16]. Moreover, high lead contamination in soil [17], water [18], air [19], herbal products [20], lead acid batteries [21], paints [22], cosmetics mainly (Kohl, lipsticks sindoor, hair dye) [23], and utensils have been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of RC (%) with low levels of Hb%, hematocrit and RBC count were observed in populations exposed to lead from cooking utensils, indigenous medicinal powder (37), lead poisoning cases (38) and lead batteries (23). The literature reports a positive and significant association (> 30 μg/dL) between BLL and RC (%) in lead battery workers (22).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the use of metallic pipes for plumbing is a major concern, especially the lead-containing outdated fixtures and solders leach out lead into the drinking water. Rolston (2011) in his study on some of the unusual sources of lead poisoning describes one of the cases of a 30-year-old male healthy office worker experiencing constant non-colicky lower abdominal pain and backache for a duration of 1 month, blue lines on the gums, hypochromic and microcytic anemia and basophilic stippling. Authors scrutinized further to reveal the source exposure and reported "rasam" cooked in a vessel coated with lead was the cause of lead poisoning.…”
Section: Lead Poisoning In Non-occupational Exposed Individuals Causementioning
confidence: 99%